Plasmonic biosensor based on a birefringent partial-solid-core microstructured optical fiber. (26th June 2017) - Popescu, V A; Puscas, N N; Perrone, G
Abstract: We propose a new plasmonic biosensor based on a birefringent partial-solid-core microstructured optical fiber where a single core mode can interact resonantly with the corresponding plasmon mode. This structure can be scaled to a larger radius of the gold layer with simultaneous increase in the number of rings and thus of the holes. The different configurations obtained by changing the geometry and relative positions of the holes can be best exploited depending on the analyte refractive index value n a . Thus, for n a = 1.35, the advantages of the proposed plasmonic sensor are larger values of the signal-to-noise ratio, maximum value of the amplitude sensitivity, power fraction in the gold layer and transmission loss as compared with that for a solid-core microstructured optical fiber. Another advantage of the proposed plasmonic sensor for n a = 1.35 is related to the smaller values of the resonance spectral width and the difference between maximal amplitude sensitivity and resonant wavelengths.